2021
DOI: 10.3390/su13158555
|View full text |Cite
|
Sign up to set email alerts
|

IoT-Based Hybrid Renewable Energy System for Smart Campus

Abstract: There is a growing interest in increasing the penetration rate of renewable energy systems due to the drawbacks associated with the use of fossil fuels. However, the grid integration of renewable energy systems represents many challenging tasks for system operation, stability, reliability, and power quality. Small hybrid renewable energy systems (HRES) are small-scale power systems consisting of energy sources and storage units to manage and optimize energy production and consumption. Appropriate real-time mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…For example, Lai et al [98] proposed a new framework for long-term electrical power system modeling, because different energy storage technologies need to be accounted for; Petkov and Gabrielli [99] analyzed P2H as a seasonal energy storage option in low-carbon multienergy systems, where the interactions of energy carriers, such as electricity, natural gas (methane), hydrogen or heat can enable new value propositions; while Sánchez et al [100] considered methane, methanol, dimethyl ether (DME) and ammonia to determine an optimal infrastructure to provide energy storage or use these outputs in other energy applications. In line with these approaches Figure 10 showed that exploration cannot only mean technological exploration (e.g., P2L in grid-scale), but innovative approaches to system integration; for example, P2G and fossil fuel power plants [101] or developing hybrid renewable energy systems using already known technologies (e.g., wind turbines, battery storage, internet of things and diesel generators) [102]. The same will be true with the integration of novel P2X technologies, fulfilling an energy storage role, regarding which future energy systems will certainly require (1) collaborative and (2) explorative learning in practice:…”
Section: Exploration Can Be Interpreted Asmentioning
confidence: 94%
“…For example, Lai et al [98] proposed a new framework for long-term electrical power system modeling, because different energy storage technologies need to be accounted for; Petkov and Gabrielli [99] analyzed P2H as a seasonal energy storage option in low-carbon multienergy systems, where the interactions of energy carriers, such as electricity, natural gas (methane), hydrogen or heat can enable new value propositions; while Sánchez et al [100] considered methane, methanol, dimethyl ether (DME) and ammonia to determine an optimal infrastructure to provide energy storage or use these outputs in other energy applications. In line with these approaches Figure 10 showed that exploration cannot only mean technological exploration (e.g., P2L in grid-scale), but innovative approaches to system integration; for example, P2G and fossil fuel power plants [101] or developing hybrid renewable energy systems using already known technologies (e.g., wind turbines, battery storage, internet of things and diesel generators) [102]. The same will be true with the integration of novel P2X technologies, fulfilling an energy storage role, regarding which future energy systems will certainly require (1) collaborative and (2) explorative learning in practice:…”
Section: Exploration Can Be Interpreted Asmentioning
confidence: 94%
“…e convolution result is further de-linearized, and the link requires the introduction of an activation function, as shown in formula ( 4). e processed structure is then stitched to obtain the feature matrix F, as shown in formula (5).…”
Section: Computational Intelligence and Neurosciencementioning
confidence: 99%
“…With the aid of various digital and intelligent technologies, universities are gradually transitioning to the age of the smart campus. Relying on these technologies, a smart campus is an effort to create an intelligent teaching environment, intelligent management mode, and digital teaching resources to form a new ecology of learner-centered education and teaching, which is an inevitable trend for digital school reform [ 4 , 5 ]. In the intelligent campus environment, students' life and learning data will be recorded into various management systems.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the above limitations, the Internet of Things (IoT) paradigm presents advanced key solutions to establish new and accurate diagnosis systems for microscopic blood images, as is described in this study. The IoT has been deployed in diverse areas, such as smart cities [ 10 , 11 ], vehicular communications [ 12 ], smart ecosystems [ 13 ], smart farming and precision agriculture [ 14 , 15 , 16 ], and smart campuses [ 17 , 18 ]. Consequently, the Internet of Medical Things (IoMT) or smart healthcare [ 19 , 20 ] has been proposed for the improvement of quality of life for patients.…”
Section: Introductionmentioning
confidence: 99%